Analisis Pola Interaksi Edukatif Antara Guru dan Siswa dalam Pembelajaran Matematika - Erawati Erawati; Mujiyem Sapti; Puji Nugraheni (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to determine the pattern of educational interaction that occurs between teachers and students, and how the impact and factors that influence the mathematics learning process. The pattern of educational interaction is a process of teaching and learning interaction activities carried out by teachers and students in the classroom in order to influence the course of the learning process to achieve certain goals. This study uses a qualitative descriptive method. The subjects of the study were mathematics teachers and students of grade IX of SMP N 3 Nusawungu and students of grade VIII of SMP PGRI 18 Cimanggu. In determining the research subjects in this study, a purposive sampling technique was used, namely a technique for taking samples of data sources with certain considerations. Data collection techniques used observation sheets, interview guidelines, and field notes. The data analysis used was a qualitative descriptive data analysis based on Flanders' analysis theory. The results of this study are that educational interactions that occur in mathematics learning produce 3 interaction patterns, namely teacher-centered interaction patterns, student-centered interaction patterns, and balanced teacher-student interaction patterns. Interaction patterns will have many impacts on the learning process such as discussions between students, questions and answers between teachers and students, noise and silence. The impact will appear according to the teaching method used by the teacher, as well as factors that influence the learning process such as student attitudes, motivation, and learning approaches used.